Implementation of the Self Organized Learning Environment (SOLE) learning model at MTs bilingual sabilil khoir - Ifa Dwi Mahfudhoh; Risdiana Chandra Dhewy (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2022)
Along with the development of education in Indonesia, teachers must prepare interesting learning strategies in order to facilitate the learning process and delivery of material to students. Not only teachers but students must also actively participate in the learning provided by the teacher. The SOLE learning model is a learning model created so that students can organize themselves into groups and learn to use smartphones connected to the internet with teacher guidance. The purpose of this study is to see the implementation of SOLE learning in terms of teacher activities, student activities, student learning outcomes, and student response questionnaires. This research is included in a quantitative descriptive study conducted at MTs Bilingual Sabilil Khoir in class VII-C with a total sample of 14 students. In the implementation of the SOLE learning model in this study, the results of teacher activities showed 3.25 "good" categories. The results of student activities can be said to be effective because on average each indicator gets > 70% which can be categorized as "Active". In the classical learning outcomes section, 78.6% are said to be "complete". And in the student response section, it is said to be positive because the student response questionnaire is on the "very good" criteria. The application of the Self Organized Learning Environment (SOLE) learning model can be used as a solution to the mathematics learning model so that it is student-centered, so that students can learn independently to understand the subject and can develop their confidence.